Geotectonic evolution by asymmetric rifting of the Proterozoic Cape Smith Belt, New Quebec - Picard, Christian; Giovenazzo, Danièle; Lamothe, Daniel (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary The tectonostratigraphic units of the Cape Smith Belt are interpreted as having accumulated in two distinct basins: (1) an older northern oceanic basin in which the Purtuniqophiolite was formed; and (2) a younger southern Povungnituk - Chukotat basin. A comparison with present-day rifting processes suggests that the younger Povungnituk - Chukotat basin evolved as an asymmetric rift leading to the successive accumulation of the sediments of the Lamarche sub-group, the continental tholeiitic basalts of the Beauparlant subgroup, and the oceanic basalts of the Chukotat Group. In response to a north-south compression, the northern Chukotat Group basalts were probably subducted northward, thus initiating the development of a magmatic arc system (Parent Group).